Determination of model of competition activity of qualified runners in the marathon - Рибальченко Тетяна Петрівна (Tatiana Rybalchenko) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: to determine modes of competitive activity for marathon athletes with various qualifications. Material and Methods: the analysis of the competitive activity of 149 athletes (men) was made. The time-keeping of separate segments of the distance was measured for qualified runners, who showed results from grade I and up. Results: it was proved that the most evenly the distance was run by the most qualified runners – master of sports. A common trend of lowering of the running speed during the second half of the distance, especially at the district of the marathon from 21,097 tо 26,3 km, was observed. Conclusions: it was proved that the most rational mode of the competitive activity of qualified marathon runners is leveled running through the distance.